2018
DOI: 10.1111/apps.12176
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Performance Feedback and the Mediating Effect of Self‐Set Goals on the Primed Goal‐Performance Relationship

Abstract: The effect of feedback and a self‐set goal on the relationship between a goal primed in the subconscious and performance were examined in three laboratory experiments and one field experiment (n = 241, 465, 201, 74 respectively), using normative (bogus) and absolute feedback manipulations, and different performance tasks that were coded for both performance quality (i.e. creativity) and quantity. The hypothesis that providing feedback, a moderator in goal setting theory, amplifies the causal effect of a primed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…With regard to moderators, three laboratory experiments and a field experiment in the workplace showed that, consistent with goal setting theory, feedback moderated the effect of a goal on performance (Itzchakov & Latham, in press). Similar to Latham et al (), Itzchakov and Latham (in press) also found that subconscious goals are a foundation for the setting of consciously set goals.…”
Section: Introductionmentioning
confidence: 80%
“…With regard to moderators, three laboratory experiments and a field experiment in the workplace showed that, consistent with goal setting theory, feedback moderated the effect of a goal on performance (Itzchakov & Latham, in press). Similar to Latham et al (), Itzchakov and Latham (in press) also found that subconscious goals are a foundation for the setting of consciously set goals.…”
Section: Introductionmentioning
confidence: 80%
“…As a way of testing our hypotheses holistically, we followed Goh, Hall, and Rosenthal's (2016) recommendation to conduct a mini meta-analysis of our studies (cf. Itzchakov & Latham, 2018). Following Goh et al, we performed a separate random-effects meta-analysis for each regression path in our model (testing H1-H3).…”
Section: Mini Meta-analysismentioning
confidence: 99%
“…This research also found that the degree of difficulty connoted by a prime (i.e., weight lifting) affected the conscious choice of a difficult versus an easy goal, as well as the effort expended to perform it, two mediators in GST. In both that experiment and the experiment involving performance feedback (Itzchakov & Latham, 2019), a self‐set goal mediated the primed goal‐performance effect.…”
Section: Introductionmentioning
confidence: 88%
“…Causal additive effects for these two goals, conscious and subconscious, have been found in both laboratory (e.g., Ganegoda, Latham, & Folger, ; Stajkovic, Locke, & Blair, ) and field experiments (e.g., Shantz & Latham, , ; Stajkovic, Latham, Sergent, & Peterson, ). GST moderators such as performance feedback and goal commitment have been shown to moderate the primed goal‐performance relationship (Itzchakov & Latham, 2019; Latham, Hu, & Brcic, 2019, respectively).…”
Section: Introductionmentioning
confidence: 99%